Suzlon : an Indian wind energy company goes global - Barton-Sweeney, Alexandra; Elias, Jaan; Bagley, Constance E.; Rae, Douglas W. ([London] : SAGE, 2016)
Suzlon, an India-based wind energy company, had made quite a splash in its first three-and-a-half years on the international stage. By the end of 2007, the company was the market leader in Asia and had completed projects in 14 countries across five continents. But many investors believed these first years were just a warm-up for what was to come (the company's market capitalization had doubled since its IPO in 2005). Global demand for wind energy remained strong and Suzlon had added significant capacity. This study examines the company's role in the sector.
Originally Published in: Barton-Sweeney, A., Elias, J., Bagley, C. E., & Rae, D.W. (2008). Suzlon: An Indian Wind Energy Company Goes Global. 08-009. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Suzlon (Firm); Wind power -- Economic aspects -- Case studies; Strategic planning -- Case studies; International business enterprises -- Case studies